Indigenous normative system: An analysis of the customary law and life plan of the Azcimmo community - Araque Chacón, Andrea Carolina; Becerra Galvis, Zaidly Yurley; Pardo García, Aldo (Sello Editorial Unipamplona, 2025)
The book addresses the normative, epistemological, and methodological aspects of the Azcimmo Indigenous Community’s life plan and internal regulations, analyzing their construction and regulation at both the international and national levels. The book examines the historical and legal background, with an emphasis on international and national legislation that supports the right of Indigenous peoples to self government and the preservation of their social structures. The ONIC’s Self Government Law is a key component, establishing the legal framework for Indigenous autonomy in Colombia. The theoretical framework focuses on the characteristics and stages of the construction of the life plan and internal regulations, whose objective is to preserve the identity, territory, and social organization of the communities, promoting their selfdetermination and strengthening. At the methodological level, the book explores the approaches used for the creation and implementation of these plans, considering the fundamental principles of Indigenous peoples and their social and territorial dynamics. Indigenous legislation, particularly indigenous law, plays an essential role in the enforcement of internal regulations, establishing a system of sanctions that regulates misconduct within communities, thus ensuring their autonomy and cohesion.